Characteristics of suspended sediment in Sentinel-1 synthetic aperture radar observations. Issue 11 (2nd November 2021) - Shao, Weizeng; Zhao, Chi; Jiang, Xingwei; Sun, Zhanfeng; Wang, Xiaoqing; Wang, Jian; Cai, Lina
ABSTRACT: The main purpose of this study is to quantitatively examine the characteristics of suspended sediment on synthetic aperture radar (SAR) observations of sea roughness. In this work, seven Sentinel-1 (S-1) SAR images in 2019 acquired in the Interferometric Wide-swath (IW) mode at vertical-vertical (VV) polarization channel were collected, where Yangtze River freshwater dominants and suspended sediment concentration (SSC) are higher in continental shelf of East China Sea (ECS). These images were collocated with waves simulated from WAVEWATCH-III (WW3) and SSC inverted from the Haiyang-1C (HY-1C) Coastal Zone Imager (CZI) image. The comparison of WW3-simulated SWH yielded a 0.45-m root-mean-square error (RMSE) with a 0.78 correlation (COR) when comparing the simulations with the measurements from Haiyang-2B (HY-2B). The SAR-measured normalized radar cross-section (NRCS) is linearly related with the HY-1 C SSC at SSC > 1200 mg l –1, which is caused by the change of dielectric constant of sea water and viscosity. Moreover, the NRCS is simulated by the three-scale radar backscattering model. It is generally found that HY-1 C SSC enhances the NRCS in difference between simulations and observations up to 8 dB at SSC of 2000 mg l –1, which could distort the accuracy of SAR wind retrieval.